Relationship between Grasshoppers and crops in an Agroecosystem of Tamil Nadu, India. - Sanjayan, K. P. (Beiträge zur Entomologie = Contributions to Entomology, 1994)
1. Grasshoppers were sampled in an agroecosystem of Tamil Nadu on major crops such as Oryza sativa, Arachis hypogaea, Phaseolus radiatus, Sorghum vulgare, as well as on fodder crops Coix lachryma and Panicum maximum for an entire year on a monthly basis with a view to analyse the association of plants and grasshoppers in an agroecosystem. - 2. Grasshoppers are less diverse in an agroecosystem in terms of their species composition. - 3. The total grasshopper population did not differ significantly with seasons on all the crops surveyed except A. hypogaea and P. radiatus. Also within a crop, the diversity of grasshopper species attacking it did not vary with season. - 4. The total yearly grasshopper faunal load in the agroecosystem was 1533.13. - 5. P. maximum supported maximum number of grasshoppers in the ecosystem. - 6. A bimodal distribution of diet breadth (Bi) values was observed for the grasshoppers with specialized species being more abundant on all the crops. - 7. The fraction of a plants faunal load made up of oligophagous grasshoppers showed good correlation with the fraction made up of specialist grasshoppers. Stichwörter Insect-plant relations, Orthoptera, Grasshopper diversity, density, agro-ecosystem, diet breadth, faunal load.